2020
DOI: 10.1155/2020/2148706
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] HO‐1/PINK1 Regulated Mitochondrial Fusion/Fission to Inhibit Pyroptosis and Attenuate Septic Acute Kidney Injury

Abstract: Background. Endotoxin-associated acute kidney injury (AKI), a disease characterized by marked oxidative stress and inflammation disease, is a major cause of mortality in critically ill patients. Mitochondrial fission and pyroptosis often occur in AKI. However, the underlying biological pathways involved in endotoxin AKI remain poorly understood, especially those related to mitochondrial dynamics equilibrium disregulation and pyroptosis. Previous studies suggest that heme oxygenase- (HO-) 1 confers cytoprotecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Similar to the effect of Mdivi-1, Znpp (an HO-1 inhibitor) could reverse the mitochondrial division and pyroptosis caused by LPS. These studies suggest that in septic kidneys, excessive mitochondrial division may also have a negative effect on the fate of cells ( 181 ).…”
Section: Cellular Processes Interact With Programmed Cell Deathmentioning
confidence: 99%
“…Similar to the effect of Mdivi-1, Znpp (an HO-1 inhibitor) could reverse the mitochondrial division and pyroptosis caused by LPS. These studies suggest that in septic kidneys, excessive mitochondrial division may also have a negative effect on the fate of cells ( 181 ).…”
Section: Cellular Processes Interact With Programmed Cell Deathmentioning
confidence: 99%
“…Mitochondria are highly dynamic organelles undergoing coordinated cycles of fission and fusion to support normal cellular functions. Mitochondrial dynamics are altered during AKI, leading to mitochondrial fragmentation and promoting damage and apoptosis of renal tubular cells (16)(17)(18). Impaired mitochondrial fusion is a crucial contributor to mitochondrial fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological inhibition of the Mfn-2/mTORC2/Akt pathway attenuated tumor growth ( Xu et al, 2017 ). Several other studies also indicated that Mfn-2 interacted with the proapoptotic Bcl-2 family members Bax and Bak ( Suen et al, 2008 ; Li et al, 2020 ).…”
Section: Mitofusin-2 and Cancermentioning
confidence: 92%